An optimization model to select policies for cervical cancer prevention and surveillance in Colombia (2018)
"The degree project carried out consists of the design of a linear optimization model for the selection of Cervical Cancer screening and detection policies in Colombia. That said, the research had a model design based on population information, budget, demographic characteristics and infection of the country, this information allows adjusting the model to the real situation of the country. The definition of the objectives of the model was directly linked to the interests of all the actors involved in the model such as the Ministry of Health, the National Institute of Cancerology and women who have or may have the disease during their life. However, the main objective is to contribute to the development of optimal intervention policies that can be carried out and that can minimize the impact of Cervical Cancer to the Colombian population. Additionally, the model is designed to be completely re-parametrized with the aim that future research can be carried out that can complement it and thus improve its results. In accordance with the aforementioned, the research work is highly aligned in most of the components with the learning goals of the University."-- Tomado del Formato de Documento de Grado